PENGARUH MANAJEMEN LABA TERHADAP KINERJA KEUANGAN DENGAN SKOR PENGUNGKAPAN ESG SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2019-2023) - Eulis Teti Hermayanti; Faisal Faisal (Diponegoro Journal of Accounting, 2025)
This study examines the effect of earnings management on financial performance, with ESG disclosure scores as a moderating variable. The dependent variables include ROA, ROE, and Tobin’s Q, while earnings management is measured using the Modified Jones Model (Dechow et al., 1995). ESG disclosure scores are obtained from Bloomberg.The sample consists of manufacturing companies listed on Indonesia Stock Exchange from 2019 to 2023, selected using purposive sampling, resulting in 90 firm-year observations. Data were analyzed using multiple regression analysis and Moderated Regression Analysis (MRA) with the absolute difference method. All analysis were conducted using SPSS version 26.The result indicate that earnings management negatively affects ROA and ROE, but has no significant effect on Tobin’s Q. Furthermore, ESG disclosure scores do not moderate the relationship between earnings management and financial performance.